FABRICATION OF FIBER OPTIC BASED SPR SENSOR USING AG/AU BIMETALLIC THIN FILMS FOR GLYCERIN DETECTION - Gemilang, Briana
Optical biosensors offer significant benefits over conventional analytical techniques due to their advantages in detecting in real time and label-free for a wide range of chemical and biological substances. Surface Plasmon Resonance (SPR) based sensors have received particular attention in their development. SPR sensors are susceptible to changes in the refractive index at the interface between the metal layer and the dielectric medium. One type of SPR sensor that has recently been developed is an optical fiber-based SPR sensor. Compared to conventional